Anaerobic membrane bioreactor (AnMBR) scale-up from laboratory to pilot-scale for microalgae and primary sludge co-digestion: Biological and filtration assessment. (November 2020) - Serna-García, R.; Mora-Sánchez, J.F.; Sanchis-Perucho, P.; Bouzas, A.; Seco, A.
Graphical abstract: Highlights: Microalgae and primary sludge co-digestion at 35 °C showed high biodegradation (65%). Same biodegradability was observed when digesting Chlorella or Scenedesmus. Higher annual costs were found operating at 100 d SRT compared to 70 d. 5.5-fold increase in energetic demand was found operating at 55 °C compared to 35 °C. No fouling formation was observed when applying gas sparging and backwashing. Abstract: This research work proposes the scale-up evaluation in terms of biological and filtration performance from laboratory to pilot-scale of an anaerobic membrane bioreactor (AnMBR) co-digesting raw microalgae and primary sludge. Best operating conditions for this scale-up were energetically and economically assessed based on laboratory results. Economic balance showed 3% higher annual costs when operating a reactor at 100 d solids retention time (SRT) compared to 70 d SRT. Energetic balance showed a 5.5-fold increase in heat demand working at thermophilic temperature comparing to mesophilic. The AnMBR operating conditions were set at 70 d SRT and 35 °C. The pilot-scale and lab-scale co-digesters performed similarly in terms of biogas production and system stability. 154 mLbiogas·d −1 ·L −1 reactor were produced at pilot-scale, corresponding to methane yield of 215 mLCH4 ·gCODinf −1 . AnMBR filtration at both laboratory and pilot-scale showed stability working at permeate fluxes of 4.2–5.8 L·m −2 ·h −1 .